PELATIHAN MEDIA FLIPBOOK CERITA DIGITAL RAMAH ANAK USIA DINI (AUD) BAGI GURU PAUD - Ermawati Zulikhatin Nuroh; Arifin Mado; Wahdatul Islamiah; Romadhoni Lailatul Maghfiroh; Hidayatul Munawaroh (COMMUNITY : Jurnal Pengabdian Kepada Masyarakat, 2026)
ABSTRACT This community service activity aims to improve the digital literacy and pedagogical creativity of early childhood education (ECE) teachers through training in creating child-friendly digital story flipbooks. The program was implemented at KB-TK Aisyiyah 25 Wage, Sidoarjo, involving 17 teachers over two days through training, hands-on practice, mentoring, and evaluation. The training materials included strengthening digital literacy, utilizing Canva and Gemini Storybook, developing prompts, and integrating flipbooks into learning activities. Evaluation used pre- and post-test questionnaires, observations, and semi-structured interviews. The results showed an increase in teachers’ digital competence from an average of 42% to 85%. All participants successfully produced at least one interactive flipbook containing text, illustrations, and audio narration. In addition, teachers demonstrated increased self-confidence, creative ideas, and readiness to implement digital media in teaching and learning activities. These findings confirm that practice-based training and mentoring are effective in encouraging learning innovation in early childhood education. The program also strengthens teachers’ capacity to use technology contextually and sustainably to create more engaging, interactive, and developmentally appropriate early childhood learning experiences. ABSTRAK Kegiatan pengabdian ini bertujuan meningkatkan literasi digital dan kreativitas pedagogis guru PAUD melalui pelatihan pembuatan media flipbook cerita digital ramah anak usia dini. Program dilaksanakan di KB-TK Aisyiyah 25 Wage, Sidoarjo, dengan melibatkan 17 guru selama dua hari melalui pelatihan, praktik langsung, pendampingan, serta evaluasi. Materi pelatihan meliputi penguatan literasi digital, pemanfaatan Canva dan Gemini Storybook, penyusunan prompt, dan integrasi flipbook ke dalam pembelajaran. Evaluasi menggunakan angket pre-test dan post-test, observasi, dan wawancara semi-terstruktur. Hasil menunjukkan peningkatan kompetensi digital guru dari rata-rata 42% menjadi 85%. Seluruh peserta berhasil menghasilkan minimal satu flipbook interaktif yang memuat teks, ilustrasi, dan audio narasi. Selain itu, guru menunjukkan peningkatan rasa percaya diri, ide kreatif, dan kesiapan menerapkan media digital dalam kegiatan belajar mengajar. Temuan ini menegaskan bahwa pelatihan berbasis praktik dan pendampingan efektif mendorong inovasi pembelajaran di PAUD. Program ini juga memperkuat kapasitas guru dalam memanfaatkan teknologi secara kontekstual dan berkelanjutan untuk menciptakan pembelajaran yang lebih menarik, interaktif, dan sesuai dengan karakteristik anak usia dini.